MACROSCOPIC AND QUALITATIVE PHYTOCHEMICAL EXAMINATION OF RED BETEL LEAVES AND GREEN BETEL LEAVES AS HERBAL MEDICINE FOR GINGIVITIS - Frita Ferlita Shafri Djohan; Herryawan; Fahrauk Faramayuda (Journal of Health and Dental Sciences, 2022)
ABSTRACT Gingivitis is inflammation of the gums that occurs in response to plaque bacteria that become more easily accumulated and difficult to clean in the gum area. The Red betel plant (Piper crocatum) and green betel leaf (Piper betle L.) are plant species from the Piperaceae family empirically used as antibacterial in gingivitis patients due to the presence of secondary metabolite compounds used as medicine. This study aims to determine the macroscopic description and the content of qualitative phytochemical compounds in red betel leaf and green betel leaf. The research method of this study was a laboratory experiment. The red and green betel leaves from Manoko Lembang, West Java, were examined for macroscopic images in color, smell, taste, and leaf size. A betel leaf qualitative phytochemical examination of flavonoids, alkaloids, flavonoids, tannins, polyphenols, saponins, and quinones. The results of the macroscopic analysis showed that the red betel leaf was green and silver with red grooves, the aromatic smell of betel, bitter taste, and the average leaf size was 3x5 cm. The green betel leaf was green, had a distinctive smell of betel slightly bitter taste accompanied by spicy, and the average leaf size was 2x4 cm. Qualitative phytochemical examination showed that red and green betel leaves contain compounds containing alkaloids, flavonoids, tannins, polyphenols, saponins, and quinones. It is necessary to examine the quantity of quantitative phytochemical components, so their potential as a gingivitis herbal medicine is clear. DOI : 10.54052/jhds.v2n2.p355-364